Troubleshooting for bleeding in thoracoscopic anatomic pulmonary resection. (January 2017) - Igai, Hitoshi; Kamiyoshihara, Mitsuhiro; Ibe, Takashi; Kawatani, Natsuko; Osawa, Fumi; Yoshikawa, Ryohei
Introduction: The objective of this study was to evaluate intraoperative vessel injury and assess troubleshooting during thoracoscopic anatomic pulmonary resection. Methods: Between April 2012 and March 2016, 240 patients underwent thoracoscopic anatomic lung resection, 26 of whom were identified as having massive bleeding intraoperatively. We analyzed the injured vessel and the hemostatic procedure employed, then compared the perioperative outcomes in patients with ( n  = 26) and without ( n  = 214) vessel injury. In addition, we compared perioperative results based on the period when surgery was performed: early period: April 2012 to March 2014 ( n  = 93) or late period: April 2014 to March 2016 ( n  = 146). Results: The surgical procedures included 20 lobectomies and 6 segmentectomies. One of the 26 patients had vessel injury at 2 points, giving a total of 27 points of injury. Hemostasis was mostly achieved by application of thrombostatic sealant (63.0%). There were no significant differences in the length postoperative hospitalization ( p  = 0.67) or morbidity rate ( p  = 0.43) between the vessel injury and the no-vessel injury groups. There were no significant differences in the incidence of significant intraoperative bleeding ( p  = 0.13) and total blood loss ( p  = 0.13) between the early and late periods. Conclusions: Application of thrombostatic sealant is one of the useful methods to achieve hemostasis during thoracoscopic anatomic pulmonary resection. Vascular hazards are inherent to a thoracoscopic approach. Therefore, thoracic surgeons should always be concerned about significant intraoperative bleeding and treat it appropriately.